Tolok Ukur Kebaruan Dalam Desain Industri - Liona Isna Dewanti (Fakultas Hukum Universitas Islam Indonesia, 2007)
Novelty test becomes legal principle that needs attention in protection of industrial design. Only the newest design gets the rights. In fact, although industrial design has been registered on Directorate General of Intellectual Property Rights, it often happens that a claim relates to the legal test of novelty on industrial design. There are no clear parameters of novelty on Industrial Design in the Act Number 30 Year 2000. The following article examines the legal test of novelty on industrial design. Therefore, the question, what is the legal test of novelty on industrial design? Unclear parameter about novelty arising difficulties in deciding the new industrial design.